2014
DOI: 10.1111/add.12646
|View full text |Cite
|
Sign up to set email alerts
|

Striking subgroup differences in substance‐related mortality after release from prison

Abstract: In Australia, patterns of substance-related death in ex-prisoners differ markedly according to Indigenous status. Efforts to prevent substance-related deaths in ex-prisoners should consider heterogeneity in the target population and tailor responses accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Importantly, those with a substance use disorder were significantly more likely to report intoxication at the time of their arrest. Coupled with well-established evidence of substance-related morbidity and mortality after release from custody (Kinner et al 2011; Forsyth et al 2014; Winter et al 2015) it seems logical that a focus on the provision of adequate and culturally appropriate drug and alcohol interventions would not only serve as an important public health intervention, but assist in reducing the incarceration (and re-incarceration) rate of Indigenous people (National Indigenous Drug and Alcohol Council 2014; Kinner and Wang 2014). …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, those with a substance use disorder were significantly more likely to report intoxication at the time of their arrest. Coupled with well-established evidence of substance-related morbidity and mortality after release from custody (Kinner et al 2011; Forsyth et al 2014; Winter et al 2015) it seems logical that a focus on the provision of adequate and culturally appropriate drug and alcohol interventions would not only serve as an important public health intervention, but assist in reducing the incarceration (and re-incarceration) rate of Indigenous people (National Indigenous Drug and Alcohol Council 2014; Kinner and Wang 2014). …”
Section: Discussionmentioning
confidence: 96%
“…The return to risky substance use after release from custody is common and predictable (Kinner 2006; Thomas et al 2013), as is the high rate of mortality and morbidly of Indigenous Australians following release from custody (Kinner et al 2011; Alan et al 2011; Forsyth et al 2014). A recent national review of supply, demand and harm reduction strategies in Australian prisons identified limitations in culturally appropriate approaches to drug and alcohol services for Indigenous Australians and no substantial focus on continuity of care into the community (Rodas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, problematic drug use significantly predicted violent re-offending. Substance abuse is regularly linked to criminal behaviour for Aboriginal offenders (AIHW 2015b; Ferrante 2013; Indig et al 2010) and post-release mortality (Forsyth et al 2014). Findings suggest that substance abuse treatment in prison appears to not be meeting the needs of Indigenous prisoners.…”
Section: Discussionmentioning
confidence: 99%
“…For ex-prisoners the post-release period is associated with a high risk of poor health and social outcomes, high rates of hospitalisation for mental health problems, substance-related problems and injury, and a markedly increased risk of death, most often due to drug overdose, suicide or preventable injury (Alan, Burmas, Preen, & Pfaff, 2011;Cutcher, Degenhardt, Alati, & Kinner, 2014;Forsyth, Alati, Ober, Williams, & Kinner, 2014). Research and service delivery attention is increasingly being directed toward examining programmes that may improve access to health services, reduce mortality and produce better outcomes when individuals are transitioning to the community (Angell, Matthews, Barrenger, Watson, & Draine, 2014).…”
Section: Introductionmentioning
confidence: 99%